Meneladani Kesabaran dan Ketabahan Rasul Ulul ‘Azmi dalam Berdakwah: Studi Kisah-Kisah dalam Al-Qur’an - M.Abduh Amrie (UIN Antasari Banjarmasin, 2017)
One of the basic substative content of the Qur'an is the the story of the past as a form of dakwah methods of the Qur'an to mankind. Among the story is about the Apostles of Ulul 'Azmi. They were included Noah, Moses, Abraham, Isa, and the Muhammad. They were all prophets and messengers who faced the strong challenges and opposition from their people, but thanks to their courage and patience they remained strong and continued to fight for the sake of upholding the Tawheed on this earth. Their character should be followed by every person who wants to take part in the field of dakwah and concentrate on calling people to the religion of Allah.